Metal- and halide-free, solid-state polymeric water vapor sorbents for efficient water-sorption-driven cooling and atmospheric water harvesting. Issue 5 (10th March 2021) - Wu, Mengchun; Li, Renyuan; Shi, Yusuf; Altunkaya, Mustafa; Aleid, Sara; Zhang, Chenlin; Wang, Wenbin; Wang, Peng
Abstract : Metal- and halide-free, solid-state polymeric water vapor sorbents are developed with improved water sorption capacity, reduced corrosivity, and solid state, leading to efficient water-sorption-driven cooling and atmospheric water harvesting. Abstract : Metal- and halide-free, solid-state water vapor sorbents are highly desirable for water-sorption-based applications, because most of the solid sorbents suffer from low water sorption capacity caused by their rigid porosity, while the liquid sorbents are limited by their fluidity and strong corrosivity, which is caused by the halide ions. Herein, we report a novel type of highly efficient and benign polymeric sorbent, which contains no metal or halide, and has an expandable solid state when wet. A group of sorbents are synthesized by polymerizing and crosslinking the metal-free quaternary ammonium monomers followed by an ion-exchange process to replace chloride anions with benign-anions, including acetate, oxalate, and citrate. They show significantly reduced corrosivity and improved water sorption capacity. Importantly, the water sorption capacity of the acetate paired hydrogel is among the best of the literature reported hygroscopic polymers in their pure form, even though the hydrogel is crosslinked. The hydrogel-based sorbents are further used for water-sorption-driven cooling and atmospheric water harvesting applications, which show improved coefficient of performance (COP) and high freshwater production rate, respectively. The results of this work would inspire more research interest in developing better water sorbents and potentially broaden the application horizon of water-sorption-based processes towards the water-energy nexus.